Correlation Between iXip and Final Pathology in Patients Affected by Prostate Cancer Undergoing Radical Prostatectomy: A Multicenter Prospective Trial (PROXIMA—PROstate iXip Index Multicenter Analysis) - Francavilla, Simone; Lonati, Chiara; Sandri, Marco; Abate, Andrea; De Marzo, Enrico; Palumbo, Carlotta; Aretano, Lucia; Belotti, Stefano; Peroni, Angelo; Peviani, Alessandro; Ferretti, Stefania; Da Pozzo, Luigi Filippo; et al. (Frontiers in Urology, 2022)
The Immune compleX Predictive Index (iXip) is a predictive tool for prostate cancer (PCa) diagnosis that integrates PSA, PSA-IgM, prostate volume and patient age. The aim of the study was to assess the correlation between iXip and clinically significant PCa in patients who underwent radical prostatectomy. A prospective multicenter study was conducted from February 2018 to August 2019 enrolling 235 patients. Stepwise-selected predictors were used to estimate multivariate regression models for each outcome, the reference model with only the set of predictors and the same model with the addition of iXip. The prediction accuracy of the two models was assessed calculating the partial area under the Receiver Operating Characteristic curve. The ROC Curve analysis showed significant differences in terms of Partial Area Under the Curve between iXip and pathological Gleason Score ≥ 7 and between iXip and tumor volume ≥ 2.5 mm3. The scatter plot analysis showed a positive linear correlation between iXip and tumor volume (considered as a continuous variable). The subpopulations with pT3-4 disease, cT3 disease and with positive surgical margins showed a significant linear relationship between iXip and tumor volume. We found elements supporting a possible correlation between iXip and aggressive PCa in terms of Gleason Score ≥ 7 and tumor volume ≥ 2.5 mm3.